Резонаторні та хвилеводні мікрохвильові сенсори в дослідженні властивостей напівпровідників - Оксенюк. А.; Бабиченко, С. В. (ХНУРЕ, 2025)
The study of electrophysical properties of semiconductor materials using microwave sensors is a promising direction due to its versatility and wide range of capabilities. The methodology allows working with various types of semiconductors, does not impose strict limitations on sample shapes, and provides the opportunity for non-electrode measurements, which enhances the accuracy of the analysis. This paper discusses resonator and waveguide microwave sensors for the diagnostics of semiconductor and dielectric materials. Approaches to improving measurement accuracy are proposed. The results obtained contribute to the advancement of diagnostic methods for the electrophysical properties of materials and expand their areas of application.
Keywords: мікрохвильовий сенсор; дослідження властивостей напівпровідників